Implementation Of Islamic Legal Principles In Islamic Education Management In The Digital Era: Implementasi Prinsip Hukum Islam dalam Manajemen Pendidikan Islam di Era Digital - Dhani Sudirman; Ricki Faisal; Hasan Al Banna; Rendi Atnanto; Mia Audina Musyadad (Jurnal Keislaman, 2025)
Islamic education management in the digital era faces various challenges in maintaining harmony between the use of technology and the principles of Islamic law, which must be maintained. Technology provides easy access to information and learning, but on the other hand, there is a potential risk of negative influences that can shift Islamic values if not managed wisely and in accordance with sharia. This study aims to analyze the implementation of Islamic legal principles in Islamic education management at SMPIT Al Muslih and to identify the challenges and solutions faced in integrating technology with Islamic values. The research method used was a qualitative approach with a case study. Data were collected through observation and in-depth interviews with administrators and educators at SMPIT Al Muslih. Data analysis was conducted using descriptive qualitative techniques. The results show that SMPIT Al Muslih has attempted to implement Islamic legal principles in educational management by paying careful attention to the use of technology. Technology is used to support the learning process and educational management, while maintaining compliance with sharia values. However, there are challenges related to inadequate regulations and low digital competence among educators. This hampers the optimal implementation of Islamic legal principles in educational management. The implications of this research indicate the need to develop policies and regulations that are adaptive to technological developments, while maintaining the integrity of Islamic values.